Bacterial community and genome analysis of cytoplasmic incompatibility-inducing Wolbachia in American serpentine leafminer, Liriomyza trifolii - Pramono, Ajeng K.; Hidayanti, Ardhiani K.; Tagami, Yohsuke; Ando, Hiroki (Frontiers in Microbiology, 2024)
Liriomyza trifolii, an agricultural pest, is occasionally infected by Wolbachia. A Wolbachia strain present in Liriomyza trifolii is associated with cytoplasmic incompatibility (CI) effects, leading to the death of embryos resulting from incompatible crosses between antibiotic-treated or naturally Wolbachia-free strain females and Wolbachia-infected males. In this study, high-throughput sequencing of hypervariable rRNA genes was employed to characterize the bacterial community in Wolbachia-infected L. trifolii without antibiotic treatment. The analysis revealed that Wolbachia dominates the bacterial community in L. trifolii, with minor presence of Acinetobacter, Pseudomonas and Limnobacter. To elucidate the genetic basis of the CI phenotype, metagenomic sequencing was also conducted to assemble the genome of the Wolbachia strain. The draft-genome of the Wolbachia strain wLtri was 1.35 Mbp with 34% GC content and contained 1,487 predicted genes. Notably, within the wLtri genome, there are three distinct types of cytoplasmic incompatibility factor (cif) genes: Type I, Type III, and Type V cifA;B. These genes are likely responsible for inducing the strong cytoplasmic incompatibility observed in L. trifolii.